Immunological and biochemical markers in preeclampsia - Kestlerová, A; Feyereisl, J; Frisová, V; Měchurová, A; Šůla, K; Zima, T; Běláček, Jaromír; Madar, J (Journal of reproductive immunology, 2012)
A basic precondition for the development of preeclampsia is the presence of placental trophoblast cells in the maternal blood circulation. On the other hand, while trophoblast cells are present in the blood of all pregnant women, preeclampsia occurs in only 2-5% of them. Evidently, other factors play a crucial role. The aim of this study was to compare a set of selected immunological factors (anti-cardiolipin autoantibodies, trophoblast-induced cell-mediated immunity, C3 and C4 complement components) and biochemical factors (serum immunoglobulins IgA, IgG, IgM) among three groups of women with uncomplicated pregnancy, gestational hypertension, or preeclampsia. Blood samples were taken 2-12h before delivery. In the preeclampsia group, there was a significantly higher number of women positive for anti-cardiolipin autoantibodies, trophoblast-induced cell-mediated immunity was elevated, serum IgG was elevated and C4 complement component was reduced. We conclude that both elevated autoimmune reactivity and the higher immune reactivity to trophoblast may contribute to the onset of preeclampsia.
Keywords: dospělí; těhotenství; kardiolipiny; Complement C3; Humans; Trophoblasts; Pre-Eclampsia; Immunity, Cellular; Cardiolipins; mladý dospělý; trofoblasty; komplement C3; komplement 4; Adult; Autoantibodies; Complement C4; imunoglobuliny; preeklampsie; buněčná imunita; biologické markery; autoprotilátky; ženské pohlaví; lidé; Pregnancy; Biomarkers; Young Adult; Immunoglobulins; Female